Avaliação de peptídeos recombinantes e sintéticos na proteção da cisticercose em modelo experimental Murino - Manhani, Marianna Nascimento (2013)
Human cysticercosis is caused by installation of metacestodes of Taenia solium. The most serious condition is the infection of the central nervous system, which leads to neurocysticercosis. Despite attempts to eradicate the disease, cysticercosis remains a serious public health issue, and the development of a vaccine may be an alternative to control the disease. The aim of this study was to test the feasibility of mimotope Cc48 from T. solium to control of experimental murine cysticercosis. Peptide Cc48 was tested as expressed in bacteriophage M13 (mCc48) and as a synthetic peptide (sCc48). A total of 160 BALB/c mice were used, being divided into four groups: G1 (n = 40): mice immunized with mCc48, G2 (n = 40): immunized with peptide Cc48, G3 (n = 40) and G4 (n = 40): inoculated with saline. After immunization, mice from groups G1, G2 and G3 were challenged with Taenia crassiceps metacestodes, while those in group G4 did not received cysticercus for being the negative control of the experiment. The animals were sacrificed at four points: 15, 30, 45 and 60 days after infection (dai), to collect blood samples and perform cysticerci count. The count of cysticerci was used to analyze the protection achieved by immunization. Serum samples were obtained from collected blood and were tested by ELISA to verify the production of antibodies (IgM, IgG, IgA, and IgE), test IgG avidity and quantify cytokines (IL-4, INF-gamma). Total and differential leukocyte counts were performed in blood samples. Indirect immunofluorescence tests were done with sera from mice against cysticerci of T. crassiceps and T. solium. Immunization with sCc48 decreased the number of cysticerci and infected animals, inducing 90% of protection and efficacy of 98% in point 60 dai. G1 had higher IgM and IgG production and presence of IgE, while in G2 IgG was the main antibody detected. G1 presented significant increase in leukocytes production. IL-4 production was detected in all groups, and some animals in groups G1, G2 and G3 presented IFN-gamma. Cross-reactivity of antibodies produced with both tested species was observed through immunofluorescence. The ability of synthetic peptide sCc48 to induce protection makes it a potential compound against cysticercosis.